A site-specific agricultural water requirement and footprint estimator (SPARE:WATER 1.0) for irrigation agriculture - Multsch, S.; Al-Rumaikhani, Y. A.; Frede, Hans-Georg; Breuer, Lutz; Justus Liebig University Giessen (My University, 2013)
The water footprint accounting method addresses the quantification of water consumption in agriculture, whereby three types of water to grow crops are considered, namely green water (consumed rainfall), blue water (irrigation from surface or groundwater) and grey water (water needed to dilute pollutants). Most of current water footprint assessments focus on global to continental scale. We therefore developed the spatial decision support system SPARE:WATER that allows to quantify green, blue and grey water footprints on regional scale. SPARE:WATER is programmed in VB.NET, with geographic information system functionality implemented by the MapWinGIS library. Water requirement and water footprints are assessed on a grid-basis and can then be aggregated for spatial entities such as political boundaries, catchments or irrigation districts. We assume in-efficient irrigation methods rather than optimal conditions to account for irrigation methods with efficiencies other than 100%. Furthermore, grey water can be defined as the water to leach out salt from the rooting zone in order to maintain soil quality, an important management task in irrigation agriculture. Apart from a thorough representation of the modelling concept we provide a proof of concept where we assess the agricultural water footprint of Saudi Arabia. The entire water footprint is 17.0 km3 yrâ 1 for 2008 with a blue water dominance of 86%. Using SPARE:WATER we are able to delineate regional hot spots as well as crop types with large water footprints, e.g. sesame or dates. Results differ from previous studies of national-scale resolution, underlining the need for regional water footprint assessments.
Keywords: ddc:630